2016
DOI: 10.1519/jsc.0000000000000898
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Ability-Based Training Program in Police Force Recruits

Abstract: Orr, RM, Ford, K, and Stierli, M. Implementation of an ability-based training program in police force recruits. J Strength Cond Res 30(10): 2781-2787, 2016-Currently, police recruit physical training programs generally use group-based runs of a "1 size fit all" approach. The aim of this study was to assess the impact of an ability-based training (ABT) program, as derived from the 30-15 Intermittent Fitness Assessment, on the metabolic fitness and injury rates of police recruits undergoing basic training. Polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(176 citation statements)
references
References 23 publications
5
171
0
Order By: Relevance
“…One explored the impact of yoga over time,46 one compared CV and strength fitness training in every session versus a programme that focused on single parameters of fitness (eg, strength and power, endurance, hypertrophy) in sessions 44. One study compared combined CV and strength fitness training incorporating interval running with standard slow, longer duration running,45 and two explored combined aerobic and anaerobic programmes over time 47 48. One study evaluated a structured diet-only intervention, which compared low calorie diets with carbohydrates eaten in the evenings compared with throughout the day 36 37.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One explored the impact of yoga over time,46 one compared CV and strength fitness training in every session versus a programme that focused on single parameters of fitness (eg, strength and power, endurance, hypertrophy) in sessions 44. One study compared combined CV and strength fitness training incorporating interval running with standard slow, longer duration running,45 and two explored combined aerobic and anaerobic programmes over time 47 48. One study evaluated a structured diet-only intervention, which compared low calorie diets with carbohydrates eaten in the evenings compared with throughout the day 36 37.…”
Section: Resultsmentioning
confidence: 99%
“…Two multiple-group studies reported details on random sequence generation 42 54. Three studies blinded participants to group allocation42 45 one of which also included outcome assessment blinding 45. Three studies31 33 42 52 reported on sample representativeness and/or described sample characteristics in relation to wider area/state police data.…”
Section: Resultsmentioning
confidence: 99%
“…VJ height, maximum number of push-ups and sit-ups completed in 1 minute, 2.4-kilometer run time), which has been linked to age-related declines in aerobic and anaerobic fitness (18,31), with some research suggesting that the nature of the law enforcement occupation itself has a negative impact on fitness (38). Considering these sex and age differences, the physical training approach that is completed during LEA academy training often features a 'one-size-fits-all' approach (39). This approach could be problematic if the recruits, as suggested above, differ in their physical fitness standards, including their ability to generate power.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…As will be discussed, female recruits and older recruits preparing to enter an LEA for training should attempt to develop their upper-and lower-body power prior to the academy period as they may be deficient in these capacities when compared to other recruits in their training classes. This would be especially problematic if the training approach for the LEA is 'one-size-fits-all' (39) and given that the job demands do not vary regardless of the sex or age of the recruit (5).…”
Section: ***Insert Table 1 About Here***mentioning
confidence: 99%
“…Officers who are physically unfit may be at greater risk of injury, illness and time off work [6]. It is therefore unsurprising that in anticipation of these task-related demands, police recruits are required to undergo preliminary physical training [7], where there is an emphasis placed on producing police officers who are capable of performing the physically demanding tasks required of them in the workforce [6,8]. However, despite this emphasis, a significant decline in physical fitness is often seen during their employment, which could negatively impact occupational task performance over time [9].…”
Section: Introductionmentioning
confidence: 99%